Directed deposition of silicon nanowires using neopentasilane as precursor and gold as catalyst - Kämpken, Britta; Wulf, Verena; Auner, Norbert; Winhold, Marcel; Huth, Michael; Rhinow, Daniel; Terfort, Andreas (Beilstein Journal of Nanotechnology, 2012)
In this work the applicability of neopentasilane (Si(SiH3)4) as a precursor for the formation of silicon nanowires by using gold nanoparticles as a catalyst has been explored. The growth proceeds via the formation of liquid gold/silicon alloy droplets, which excrete the silicon nanowires upon continued decomposition of the precursor. This mechanism determines the diameter of the Si nanowires. Different sources for the gold nanoparticles have been tested: the spontaneous dewetting of gold films, thermally annealed gold films, deposition of preformed gold nanoparticles, and the use of “liquid bright gold”, a material historically used for the gilding of porcelain and glass. The latter does not only form gold nanoparticles when deposited as a thin film and thermally annealed, but can also be patterned by using UV irradiation, providing access to laterally structured layers of silicon nanowires.
Keywords: chemical vapor deposition; gold; nanoparticle; patterning; radiation-induced nanostructures; vapor-liquid-solid mechanism

(untitled) - Wind, S. J.; Appenzeller, J.; Martel, R.; Derycke, V.; Avouris, P. (Appl. Phys. Lett., 2002)

(untitled) - Cui, Y.; Lieber, C. M. (Science, 2001)

(untitled) - Li, Z.; Chen, Y.; Li, X.; Kamins, T. I.; Nauka, K.; Williams, R. S. (Nano Lett., 2004)

(untitled) - Cui, Y.; Wei, Q.; Park, H.; Lieber, C. M. (Science, 2001)

(untitled) - Cui, Y.; Zhong, Z.; Wang, D.; Wang, W. U.; Lieber, C. M. (Nano Lett., 2003)

(untitled) - Duan, X.; Huang, Y.; Cui, Y.; Wang, J.; Lieber, C. M. (Nature, 2001)

(untitled) - Baxter, J. B.; Aydil, E. S. (Appl. Phys. Lett., 2005)

(untitled) - Qi, P.; Wong, W. S.; Zhao, H.; Wang, D. (Appl. Phys. Lett., 2008)

(untitled) - Pan, H.; Lim, S.; Poh, C.; Sun, H.; Wu, X.; Feng, Y.; Lin, J. (Nanotechnology, 2005)

(untitled) - Schubert, L.; Werner, P.; Zakharov, N. D.; Gerth, G.; Kolb, F. M.; Long, L.; Gösele, U.; Tan, T. Y. (Appl. Phys. Lett., 2004)

(untitled) - Wang, N.; Tang, Y. H.; Zhang, Y. F.; Lee, C. S.; Lee, S. T. (Phys. Rev. B, 1998)

(untitled) - Hwang, N. M.; Cheong, W. S.; Yoon, D. Y.; Kim, D.-Y. (J. Cryst. Growth, 2000)

(untitled) - Wagner, R. S.; Ellis, W. C. (Appl. Phys. Lett., 1964)

(untitled) - Cui, Y.; Lauhon, L. J.; Gudiksen, M. S.; Wang, J.; Lieber, C. M. (Appl. Phys. Lett., 2001)

(untitled) - Shao, M.; Ma, D. D. D.; Lee, S.-T. (Eur. J. Inorg. Chem., 2010)

(untitled) - Liu, Z. Q.; Zhou, W. Y.; Sun, L. F.; Tang, D. S.; Zou, X. P.; Li, Y. B.; Wang, C. Y.; Wang, G.; Xie, S. S. (Chem. Phys. Lett., 2001)

(untitled) - Yao, Y.; Fan, S. (Mater. Lett., 2007)

(untitled) - Gu, Q.; Dang, H.; Cao, J.; Zhao, J.; Fan, S. (Appl. Phys. Lett., 2000)

(untitled) - Alet, P.-J.; Yu, L.; Patriarche, G.; Palacin, S.; Cabarrocas, P. R. (J. Mater. Chem., 2008)

(untitled) - Kolb, F. M.; Hofmeister, H.; Scholz, R.; Zacharias, M.; Gösele, U.; Ma, D. D.; Lee, S.-T. (J. Electrochem. Soc., 2004)

(untitled) - Zeng, X. B.; Xu, Y. Y.; Hu, Z. H.; Diao, H. W.; Wang, Y. Q.; Kong, G. L.; Liao, X. B. (J. Cryst. Growth, 2003)

(untitled) - Bandaru, P. R.; Pichanusakorn, P. (Semicond. Sci. Technol., 2010)

(untitled) - Ghosh, S. K.; Pal, T. (Chem. Rev., 2007)

(untitled) - Glass, R.; Möller, M.; Spatz, J. P. (Nanotechnology, 2003)

(untitled) - Taue, S.; Nishida, K.; Sakaue, H.; Takahagi, T. (E-J. Surf. Sci. Nanotechnol., 2007)

(untitled) - Colli, A.; Hofmann, S.; Fasoli, A.; Farrari, A. C.; Ducati, C.; Dunin-Borkowski, R. E.; Robertson, J. (Appl. Phys. A, 2006)

(untitled) - Mbenkum, B. N.; Schneider, A. S.; Schütz, G.; Xu, C.; Richter, G.; van Aken, P. A.; Majer, G.; Spatz, J. P. (ACS Nano, 2010)

(untitled) - He, J.-Y.; Lu, J.-X.; Dai, N.; Zhu, D.-M. (J. Mater. Sci., 2012)

(untitled) - Pillai, S.; Catchpole, K. R.; Trupke, T.; Green, M. A. (J. Appl. Phys., 2007)

(untitled) - Ozaki, N.; Ohno, Y.; Takeda, S. (Appl. Phys. Lett., 1998)

(untitled) - Schmidt, V.; Wittemann, J. V.; Senz, S.; Gösele, U. (Adv. Mater., 2009)

(untitled) - Hochbaum, A. I.; Fan, R.; He, R.; Yang, P. (Nano Lett., 2005)

(untitled) - Emeléus, H. J.; Steward, K. (J. Chem. Soc., 1935)

Explosive Silicon Gas Casts Shadow on Solar Power Industry (Scientific American, 2010)

(untitled) - Bloem, J.; Claassen, W. A. P.; Valkenburg, W. G. J. N. (J. Cryst. Growth, 2001)

(untitled) - Molnar, W.; Lugstein, A.; Pongratz, P.; Auner, N.; Bauch, C.; Bertagnolli, E. (Nano Lett., 2010)

(untitled) - Park, W. I.; Zheng, G.; Jiang, X.; Tian, B.; Lieber, C. M. (Nano Lett., 2008)

(untitled) - Roenigk, K. F.; Jensen, K. F.; Carr, R. W. (J. Phys. Chem., 1987)

(untitled) - Walsh, R. (Acc. Chem. Res., 1981)

(untitled) - Chung, K. H.; Yao, N.; Benziger, J.; Sturm, J. C.; Singh, K. K.; Carlson, D.; Kuppurao, S. (Appl. Phys. Lett., 2008)

Silicon-Based Epitaxy by Chemical Vapor Deposition Using Novel Precursor Neopentasilane - Chung, K. H. (Princeton University, 2010)

(untitled) - Frens, G. (Nature (London), Phys. Sci., 1973)

(untitled) - Aureau, D.; Varin, Y.; Roodenko, K.; Seitz, O.; Pluchery, O.; Chabal, Y. J. (J. Phys. Chem. C, 2010)

(untitled) - Raiber, K.; Terfort, A.; Benndorf, C.; Krings, N.; Strehblow, H.-H. (Surf. Sci., 2005)

(untitled) - Hunt, L. B. (Gold Bull., 1979)

(untitled) - Tumanov, S. G. (Glass Ceram., 1961)

(untitled) - Xia, Y.; Whitesides, G. M. (Annu. Rev. Mater. Sci., 1998)

(untitled) - Lee, J. N.; Park, C.; Whitesides, G. M. (Anal. Chem., 2003)

(untitled) - Haiss, W.; Thanh, N. T. K.; Aveyard, J.; Fernig, D. G. (Anal. Chem., 2007)

(untitled) - Winhold, M.; Schwalb, C. H.; Porrati, F.; Sachser, R.; Frangakis, A. S.; Kämpken, B.; Terfort, A.; Auner, N.; Huth, M. (ACS Nano, 2011)